Analisis Potensi Pajak Hotel dan Konstribusinya Terhadap PAD Kabupaten Badung - Iswari, Kadek Clara Sintha; Dwi Ratnadi, Ni Made (E-Jurnal Akuntansi; Vol 30 No 2 (2020), 2020)
Hotel tax is one of the regional taxes as a contributor to the Regional Original Income (PAD) which has the potential to increase in Badng Regency. The purpose of this study was to determine the hotel tax potential and its contribution in the North Kuta District of the PAD in Badung Regency. The hotel taxpayer population is 405 units. The sample is determined by the non probability sampling method with the saturated sample technique. Data collection through documentation studies and interviews. The analysis technique used is the calculation of hotel tax potential and calculation of hotel tax contributions to PAD. Based on the results of the analysis, there are potential hotel taxes that can still be explored. The contribution of the realization of hotel taxes in the North Kuta District to the Badung Regency PAD was 6.13 percent and 8.35 percent of the Badung Regency Regional tax in 2018. Keywords: Hotel Tax;  Potential; Contribution; Local Original Income.